Strategi Pemasaran dan Pengembangan Pengelolaan Garam Masyarakat dalam Meningkatkan Hasil Penjualan dan Kualitas Didesa Pemongkong: Marketing Strategy and Development of Community Salt Management to Increase Sales Results and Quality in Pemongkong Village - M. Saipul Watoni; Irwan Yon Hadi; Sahnizam; Muhammad Julianto; M. Sulamul Ghozi R (Pendidikan Al-Gafari, 2026)
This study aims to analyze the marketing strategy and development of community salt management in increasing sales results and product quality in Pemongkong Village, Jerowaru District, East Lombok Regency. This village is known as one of the centers of community salt production on Lombok Island, but still faces various problems related to business management, marketing, and product quality improvement. These problems have an impact on the low competitiveness and selling value of local salt in the market. This study uses a qualitative approach with a descriptive method. Data collection techniques were carried out through field observations, in-depth interviews with salt farmers, salt business group managers, and village officials, as well as other supporting documentation. Data analysis techniques used an interactive model that includes data reduction, data presentation, and drawing conclusions. The results show that the marketing strategy implemented by the salt farming community in Pemongkong Village is still conventional, namely through direct sales to middlemen without adequate packaging and branding. However, there are efforts to develop management, such as the implementation of a geomembrane pond system, training for salt business groups (KUB), and improving production quality. The main obstacles faced include limited market access, low marketing literacy, and limited infrastructure support.